Analysis of the functional features of the buildings of the khanaka - the institution of Sufism in Central Asia - Maxmatqulov I.T; Karimova N.A (Zien Journals, 2022)
The article analyzes the functional features of the hanaka buildings in Central Asia, as a result of which the groups of their buildings by functional feature are identified, the composition of the hanaka premises is determined and refined according to the historical architectural types of these buildings in Central Asia.
Keywords: Institute of Sufism; Central Asia; building of a khanaka; study of the topic